2003
DOI: 10.1523/jneurosci.23-11-04395.2003
|View full text |Cite
|
Sign up to set email alerts
|

Math1Gene Transfer Generates New Cochlear Hair Cells in Mature Guinea PigsIn Vivo

Abstract: Hair cell loss in the mammalian cochlea is irreversible and results in permanent hearing loss. Math1, the basic helix-loop-helix transcription factor homolog of the Drosophila atonal gene, is a positive regulator of hair cell differentiation during cochlear development. Developing hair cells express Math1, and nonsensory cells do not. We set out to determine the outcome of overexpression of Math1 in nonsensory cells of the cochlea on the phenotype of these cells. We demonstrate that in vivo inoculation of aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
270
1
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 413 publications
(287 citation statements)
references
References 29 publications
10
270
1
4
Order By: Relevance
“…As previously described, the presence of the Atoh1 plasmid induces numerous ectopic HCs (Fig. S3B,B′) (Gubbels et al, 2008;Kawamoto et al, 2003;Liu et al, 2014). This was accompanied by an expansion of the Sox2 domain on the medial side of the OC 4 days later (Fig.…”
Section: Atoh1 Can Drive Expansion Of the Medial Compartmentsupporting
confidence: 70%
“…As previously described, the presence of the Atoh1 plasmid induces numerous ectopic HCs (Fig. S3B,B′) (Gubbels et al, 2008;Kawamoto et al, 2003;Liu et al, 2014). This was accompanied by an expansion of the Sox2 domain on the medial side of the OC 4 days later (Fig.…”
Section: Atoh1 Can Drive Expansion Of the Medial Compartmentsupporting
confidence: 70%
“…In neonatal mice, supporting cells remain competent to form hair cells in response to Atoh1 overexpression, especially in the Kölliker's organ, which is directly medial to the organ of Corti (Kelly et al, 2012;Liu et al, 2012aLiu et al, , 2014Shou et al, 2003;Yang et al, 2013;Zheng and Gao, 2000). However, this competence is significantly diminished in the undamaged, mature cochlea when assessed via either a transgenic approach or direct viral inoculation (Kawamoto et al, 2003;Liu et al, 2012a).…”
Section: Kip1mentioning
confidence: 99%
“…Attempts to produce ectopic HCs in mature animals and to regenerate HCs in vivo following cochlear injury by either ototoxic drugs or excessive noise have had limited success. One group has shown that adenovirus-mediated expression of Atoh1 in mature guinea pig cochleae results in ectopic hair cells (Kawamoto et al 2003) and infecting newly injured guinea pigs with an adenovirus carrying Atoh1 leads to regeneration of HCs; however, this approach failed to restore HCs in animals with longer-term injuries or more damaged cochleae (Izumikawa et al 2005(Izumikawa et al , 2008. Replication of these results and further investigation into the requirement for SC survival may yield useful information.…”
Section: Atoh1 and Auditory Hair Cellsmentioning
confidence: 99%